Perbandingan Indeks Larva Vektor Demam Berdarah Dengue Pra dan Paska-Intervensi di Kota Prabumulih - Hotnida Sitorus; Yulian Taviv; Anif Budiyanto; Lasbudi P Ambarita; Milana Salim; Rika Mayasari (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Prabumulih city is one of dengue endemic area in South Sumatera Province with number of cases in 2011-2012 were 225 and 301 cases respectively. The research aims to determine the influence of jumantik accompanied by health promotion program to the larval mosquitoes indices. This is quasi-experimental study, carried out in three endemic areas of Prabumulih City in 2014. There were two intervention in two location and one location for non-intervention. In the first location, the intervention were larva surveillance by jumantik cadre, giving larvicide selectively, accompanied by health promotion program to community group (intervention I), in second location the intervention only for larvae surveillance by jumantik cadre (intervention II), and the third location giving no intervention. Observation of immature mosquito was carried out in every location before and after intervention was given. The result showed an increase in Free larvae index of 19,8% in the intervention I , 12,5% in the intervention II and 5,3% in the no-intervention location. Indicator of breteau index showed a decrease in all location, 73,1% in the intervention I, 62,8% in the intervention II and 10,8% in the no-intervention location. Container index indicator showed a decrease in two intervention location, 10,2% in the intervention I, 6,6% in the intervention II, while in no-intervention location show an increase for 8%. Health promotion program about how to prevent dengue transmission through potential community groups could become an alternative effort to control vector population integrated with other control methods.